Frequency and prognostic value of resistance/intolerance to hydroxycarbamide in 890 patients with polycythaemia vera. (21st December 2015) - Alvarez‐Larrán, Alberto; Kerguelen, Ana; Hernández‐Boluda, Juan C.; Pérez‐Encinas, Manuel; Ferrer‐Marín, Francisca; Bárez, Abelardo; Martínez‐López, Joaquín; Cuevas, Beatriz; Mata, M. Isabel; García‐Gutiérrez, Valentín; Aragües, Pilar; Montesdeoca, Sara; et al.
Summary: The clinical significance of resistance/intolerance to hydroxycarbamide (HC) was assessed in a series of 890 patients with polycythaemia vera (PV). Resistance/intolerance to HC was recorded in 137 patients (15·4%), consisting of: need for phlebotomies (3·3%), uncontrolled myeloproliferation (1·6%), failure to reduce massive splenomegaly (0·8%), development of cytopenia at the lowest dose of HC to achieve a response (1·7%) and extra‐haematological toxicity (9%). With a median follow‐up of 4·6 years, 99 patients died, resulting in a median survival of 19 years. Fulfilling any of the resistance/intolerance criteria had no impact on survival but when the different criteria were individually assessed, an increased risk of death was observed in patients developing cytopenia [Hazard ratio (HR): 3·5, 95% confidence interval (CI): 1·5–8·3, P  = 0·003]. Resistance/intolerance had no impact in the rate of thrombosis or bleeding. Risk of myelofibrotic transformation was significantly higher in those patients developing cytopenia (HR: 5·1, 95% CI: 1·9–13·7, P  = 0·001) and massive splenomegaly (HR: 9·1, 95% CI: 2·3–35·9, P  = 0·002). Cytopenia at the lowest dose required to achieve a response was also an independent risk factor for transformation to acute leukaemia (HR: 20·3, 95% CI: 5·4–76·5, P  < 0·001). In conclusion, the unified definition of resistance/intolerance to HC delineates a heterogeneous group of PV patients, with those developing cytopenia being associated with an adverse outcome.